Effect of calcium, magnesium, and zinc on ticarcillin and tobramycin alone and in combination against Pseudomonas aeruginosa. - Zuravleff, J J (1982)
Correlation between in vitro and in vivo test results for synergy between carboxypenicillins and aminoglycosides against Pseudomonas aeruginosa is poor. Although the divalent cation content of culture media is known to affect aminoglycoside susceptibility testing for P. aeruginosa, this effect of divalent cations has not been examined for synergy testing of carboxypenicillin-aminoglycoside interaction against P. aeruginosa. The minimal inhibitory concentrations (MICs) of tobramycin and ticarcillin and the interaction of these drugs in combination were studied by a microtitration method for 36 strains of P. aeruginosa in Mueller-Hinton broth with varying supplements of calcium, magnesium, and zinc. The supplementation of Mueller-Hinton broth to 50 or 100 mg of calcium per liter had a significant effect in increasing the tobramycin MIC (P less than 0.01), as well as decreasing the degree of synergy between ticarcillin and tobramycin (P less than 0.01). Supplementation to 20 mg of magnesium per liter, 1.0 mg of zinc per liter, or both did not significantly affect tobramycin MIC or the interaction of tobramycin and ticarcillin. Supplementation to 50 or 100 mg of calcium per liter rendered any additional effect of magnesium and zinc on aminoglycoside MIC and aminoglycoside-carboxypenicillin interaction negligible. If these results for ticarcillin and tobramycin are confirmed for other carboxypenicillins and aminoglycosides, then the Mueller-Hinton broth used for P. aeruginosa aminoglycoside susceptibility and synergy testing may need to be supplemented only with calcium at a concentration of 50 mg/liter.